Social valuation across multiple audiences: The interplay of ability and identity judgments - Fini,R; Jourdan,J; Perkmann,M (Academy of Management Journal, 2018)
How is an evaluating audience influenced by previous evaluations made by another audience? This question is critical to individuals and organizations reaching out to multiple audiences for key resources. While extant work has suggested evaluators are influenced by previous evaluations made by their peers, we develop theory about how evaluators’ assessment of a candidate is shaped by previous evaluations made by an external (nonpeer) audience. We argue that the latter represent exogenous indices that affect evaluators in two opposing ways: they positively influence peer valuation by pointing to candidates’ unobservable abilities, yet, since they are conferred by an external audience, they are also indicative of candidates’ deviation from an expected peer identity. The combination of the two opposite effects suggests an inverted U-shaped relationship between exogenous indices and peer valuation. Further, this effect is moderated by the identity proximity between audiences, and the availability of previous peer evaluations (endogenous indices). We test and find support for our arguments using unique data on the peer valuation of 9,502 academic scientists applying for research grants at a research university. Our work contributes to the understanding of valuation and socially endogenous inferences, and has implications for the management of organizations in multi-audience environments.